2007
DOI: 10.1097/01.mpg.0000237939.50791.4b
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of the Plasticizers Diethylhexylphthalate and Polyadipate From Polyvinylchloride Nasogastric Tubes Through Gastric Juice and Feeding Solution

Abstract: Within 1 week, the extraction of DEHP from a 5-cm PVC tube reaches up to 1 mg. Extrapolated, this represents an in vivo load of up to 4 mg. The load accumulated by a newborn in an intensive care unit can therefore easily reach several milligrams of DEHP per day. Polyadipate nasogastric tubes may therefore be an alternative and help to reduce the daily load of DEHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…76 This study suggested that polyadipate nasogastric tubing should be used as an alternative product in order to reduce DEHP exposure in NICU. However, critical data on developmental and reproductive toxicity for polyadipates are unavailable and potential side effects have not been assessed.…”
Section: Dehp-free Plasticizersmentioning
confidence: 90%
See 2 more Smart Citations
“…76 This study suggested that polyadipate nasogastric tubing should be used as an alternative product in order to reduce DEHP exposure in NICU. However, critical data on developmental and reproductive toxicity for polyadipates are unavailable and potential side effects have not been assessed.…”
Section: Dehp-free Plasticizersmentioning
confidence: 90%
“…7,14,76 Although a broad range of molecular weights can be obtained based on use through polycondensation, the highest molecular weight polyesters have the lowest potential for migration into a lipophilic substance of all the plasticizers discussed. 14 Polyadipates are promoted by chemical companies in Europe as a low-cost alternative to DEHP for short-term use of gastric tubes, whereas polyurethane or silicone devices are suggested for long-term tube feeding because of their durability.…”
Section: Dehp-free Plasticizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Di-(2-ethylhexyl) phthalate (DEHP), a plasticizer commonly used by industry to add flexibility to polyvinyl chloride products, is highly prevalent in the environment and is present in a wide variety of consumer products, including medical devices such as intravenous tubing, catheters, and dialysis bags [1][2][3][4]. DEHP, which has been shown to have antiandrogenic properties, exerts its effects through its metabolite mono-2-ethylhexyl phthalate (MEHP), which is formed after cleavage of one of its side chains by lipases in the gut, and is 10 times more active than the parent compound [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study, 5 cm of PVC nasogastric tubes containing DEHP or polyadipate were incubated with feeding solution and gastric juice (Subotic et al 2007). Although at least 10 times lower leaching was observed compared to that of DEHP, no conclusion can be made from this study because the contents of the two plasticizers in the tubings are not described.…”
Section: Exposure To Alternative Plasticizersmentioning
confidence: 99%